VISUAL STORYTELLING IN INDIAN FOLK ART: NARRATIVE TECHNIQUES IN KALAMKARI AND PATTACHITRA - Komal, Dr. (Journal of Creativity in Art and Design, 2024)
Indian folk art traditions such as Kalamkari and Pattachitra serve as rich visual narratives that convey myths, epics, and social messages. This research paper examines the visual storytelling techniques employed in two prominent Indian folk art traditions: Kalamkari from Andhra Pradesh and Pattachitra from Odisha. Both art forms represent rich cultural heritage with distinct narrative approaches that have evolved over centuries. Through comparative analysis, this study identifies key narrative strategies including sequential storytelling, symbolic representations, compositional hierarchy, and the integration of text with imagery. The research demonstrates how these traditional art forms function as repositories of mythological, religious, and cultural knowledge, while adapting to contemporary contexts. By examining the structural elements of visual communication within these traditions, this paper contributes to a deeper understanding of indigenous narrative aesthetics and their significance in preserving cultural identity.